1996
DOI: 10.1007/bf02447515
|View full text |Cite
|
Sign up to set email alerts
|

Scale problems in reporting landscape pattern at the regional scale

Abstract: Remotely sensed data for Southeastern United States (Standard Federal Region 4) are used to examine the scale problems involved in reporting landscape pattern for a large, heterogeneous region. Frequency distributions of landscape indices illustrate problems associated with the grain or resolution of the data. Grain should be 2 to 5 times smaller than the spatial features of interest. The analyses also reveal that the indices are sensitive to the calculation scale, i.e., the unit area or extent over which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
151
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(157 citation statements)
references
References 15 publications
1
151
1
4
Order By: Relevance
“…The importance of the scale has been widely recognised as it concerns all types of ecological data and is a fundamental aspect of the environmental heterogeneity, whose interpretation depends on the level of observation established when studying an ecological system (Battisti & Fanelli, 2015;Levin, 1992;O'Neill et al, 1991O'Neill et al, , 1996.…”
Section: Discussion: Lessons Learned and Perspectivesmentioning
confidence: 99%
“…The importance of the scale has been widely recognised as it concerns all types of ecological data and is a fundamental aspect of the environmental heterogeneity, whose interpretation depends on the level of observation established when studying an ecological system (Battisti & Fanelli, 2015;Levin, 1992;O'Neill et al, 1991O'Neill et al, , 1996.…”
Section: Discussion: Lessons Learned and Perspectivesmentioning
confidence: 99%
“…Relationships of metric responses to varying grain and extent are known to be complex, with both the metric values and distributional shape being affected ͑e.g., O'Neill et al 1996;Saura 2002;Wu et al 2002͒. For example, in an investigation involving real landscapes, Wu et al ͑2002͒ found that metrics fell into three categories of response to changing scale; responses were predictable in only one of these categories.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…While most of the MAUP studies prior to the 1990's focused on traditional statistical measures ͑e.g., mean, variance, regression and correlation coefficients͒ and spatial interaction models, scale effects have been increasingly studied using landscape metrics ͑or indices͒ in ecology, remote sensing, and geography in the past two decades ͑Meentemeyer and Box 1987; Turner et al 1989;Turner et al 2001;Bian and Walsh 1993;Moody and Woodcock 1994;Benson and Mackenzie 1995;Wickham and Riitters 1995;Jelinski and Wu 1996;O'Neill et al 1996;Qi and Wu 1996;Wu et al 2003͒. These studies have shed new light on the problems of scale effects in pattern analysis as well as the multiscaled nature of spatial heterogeneity.…”
mentioning
confidence: 99%